Embeddedness Theory dalam Menjelaskan Pengaruh Literasi Keuangan Digital, Digital Marketing, dan Kompetensi Sumber Daya Manusia terhadap Kinerja UMKM - Sawalni; Argya Najwa Setiawan; Rafi Muhammad Yusuf; Briggita Nadiansyah; Rendi Permana; Syabilla Anggi Lestari; Meissa Andina; Rizki Aidil Fitra (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a fundamental pillar of Indonesia's economy, yet their performance remains constrained by limited digital financial literacy, ineffective digital marketing implementation, and insufficient human resource competencies. This study aims to analyze the influence of digital financial literacy, digital marketing, and human resource competency on MSME performance in Bandung City through an economic sociology approach by integrating Embeddedness Theory, Resource-Based View, and Dynamic Capabilities Theory. The research employed a quantitative approach with a survey method involving 112 MSME owners in Bandung City. Data were analyzed using multiple linear regression with SPSS. The findings reveal that digital financial literacy and human resource competency exert positive and significant effects on MSME performance, while digital marketing does not demonstrate a significant direct effect. However, simultaneously, the three variables significantly influence MSME performance. These findings confirm that enhancing MSME performance requires a comprehensive approach through strengthening strategic resources and social network support. This study contributes theoretically through the integration of three theoretical frameworks and provides practical implications for stakeholders in formulating sustainable digital-based MSME development policies